Meta-Analisis: Pengaruh Waktu Tunggu Terhadap Kepuasan Pasien di Pelayanan Rawat Jalan di Fasilitas Kesehatan - Tria Fora Delfita; Trioni Widyastuti; Khairunnisa Khairunnisa (HB PRESS, 2025)
Patient satisfaction is considered a key indicator of a healthcare facility’s success. Optimizing patient waiting times is crucial to improving patient satisfaction. This study aims to analyze the effect of waiting time on the satisfaction of outpatients in hospitals. This research is a systematic review and meta-analysis study using the PRISMA diagram and PICO model. Population: outpatient patient. Intervention: short waiting time. Comparison: long waiting time. Outcome: patient satisfaction. Data were sourced from Google Scholar, PubMed, Science Direct, and Springer Link which were published from 2015-2025 using keywords waiting time AND patient AND satisfaction AND outpatient AND AOR. The result of this study from 9 primary studies were used to analyze waiting time and patient satisfaction with health services. Patient who experienced short waiting times 3,02 times more satisfied with health services compared with long waiting times (aOR=3,02; CI 95%=2,22 to 4,10; P=0.86). Conclusion: Patients with shorter wait times reported 3.02 times higher levels of satisfaction than those with longer wait times. This finding suggests that service efficiency, particularly in wait time management, is a critical component in improving patient experience and satisfaction.